2008
DOI: 10.1583/07-2215.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thoracic Aortic Aneurysm Repair:Evaluating the Utility of Intravascular Ultrasound Measurements

Abstract: IVUS measurements of the thoracic aorta were larger than CT measurements 66% of the time. However, there are 2 concerns with IVUS: off-center measurements distort the image and tangential measurements on a curve do not reflect a true centerline diameter. Thus, off-center IVUS measurements or those taken in the tortuous portion of the aorta may not be as accurate as centerline CT measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The mean diameters of the thoracic aorta determined by IVUS were larger than the CT values in 78% of cases. Fernández et al (6) previously documented a positive bias in the diameters measured by IVUS to the minimum diameter on CT in 66% of 71 measurements. Both the present and previous results emphasize that off-center measurements by IVUS lead to a distortion of the image, as they do not represent a true center-line measurement (6).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The mean diameters of the thoracic aorta determined by IVUS were larger than the CT values in 78% of cases. Fernández et al (6) previously documented a positive bias in the diameters measured by IVUS to the minimum diameter on CT in 66% of 71 measurements. Both the present and previous results emphasize that off-center measurements by IVUS lead to a distortion of the image, as they do not represent a true center-line measurement (6).…”
Section: Discussionmentioning
confidence: 94%
“…This research is supported by our results, where the highest correlation and smallest deviations were observed in the descending aorta. Fernández et al (6) reported that in 54% of cases their IVUS measurements led to a change in the selection of stent-graft size, initially chosen based on prior CT measurement. However, the bias of IVUS should be taken into account, and through understanding the pitfalls of IVUS measurement it may be possible to reduce this selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Off-center measurements or those taken in tortuous portions of the aorta (tangential measurements on a curve) do not reflect a true centerline diameter, may provide an oblique slice, and are less accurate than centerline computed tomographic measurements. 63 Another major limitation of IVUS is that it lacks Doppler capabilities (color Doppler can detect flow into small arteries, false luminal flow, and endoleaks). Last, the high cost of the disposable transducers and invasive nature of the technique limit IVUS for most clinical applications other than guidance of endovascular procedures.…”
Section: Limitationsmentioning
confidence: 99%
“…5 A recent report demonstrated significantly better mortality rates and shorter length of stay following TEVAR compared to open thoracic aneurysm repair. 6 Even as favorable mid-term data become available, 7-9 the effectiveness, national adoption, change in patient risk stratification and trends of TEVAR remain unknown.…”
Section: Introductionmentioning
confidence: 99%